Single-molecule conductance of dibenzopentalenes: antiaromaticity and quantum interference. Issue 6 (21st December 2020) - Schmidt, Maximilian; Wassy, Daniel; Hermann, Mathias; González, M. Teresa; Agräit, Nicolás; Zotti, Linda A.; Esser, Birgit; Leary, Edmund
Abstract : Single molecule junctions of antiaromatic dibenzo[ a, e ]pentalene are studied. 5, 10 connection gives high conductance, whereas 2, 7 gives low conductance due to destructive quantum interference. Comparison with aromatic analogues is made. Abstract : The effects of antiaromaticity and destructive quantum interference (DQI) are investigated on the charge transport through dibenzo-[ a, e ]pentalene (DBP). 5, 10-Connectivity gives high single-molecule conductance whereas 2, 7 gives low conductance due to DQI. Comparison of the 5, 10-DBP with phenyl and anthracene analogues yields the trend G DBP ≈ G Anth > G Ph, despite the aromatic anthracene having a larger HOMO–LUMO gap than 5, 10-DBP. This is explained by unfavourable level alignment for 5, 10-DBP.